Development of the African Digital Health Library (ADHL): Experience at the Medical Library, University of Ibadan, Nigeria (2020)
The African Digital Health Library,(ADHL) is a collaborative project involving five African institutions namely Bamako University of Science and Technology, Kenya Methodist University, Universities of Ibadan, Nairobi, Zambia, and Zimbabwe. The University of Ibadan Nigeria component of the ADHL (ADHL-UI) is described in this paper. Funded by the Office of Global AIDS Coordinator of the United States Department of State, the goal of ADHL-UI is to store, preserve, make accessible through an institutional repository, theses and dissertations by postgraduate students of the institution’s College of Medicine. The ADHL-UI has over 1000 theses and dissertations accessible on the internet. Creation of the ADHL-UI, a repository of theses and dissertations in the Medical Library, University of Ibadan, is a major contribution to research development and preservation of institutional scholarly heritage. Effective use by students and faculty will help in reducing duplication of research efforts and create visibility for the authors and the institution. Digitization, Institutional repository, University of Ibadan, African Digital Health Lib